Personal Correspondence - Abrahams, Peter (My University, 1962)
Personal Correspondence Letter to Peter Abrahams from Reggie regarding a missing parcel
2 pgs. Typescript, letter-sized, sepia-toned, in fairly good condition.
Keywords: Correspondence; Letters